Jade cool fiber and preparation method thereof
By preparing high-thermal conduction particles in the fiber and aligning them with a magnetic field to form a thermal conduction path, the problem that jade thermal fillers cannot form thermal conduction paths inside the fibers is solved, and the cooling effect and moisture-absorbing and sweating properties of the fibers are significantly improved.
Patent Information
- Application Number
- CN202510312248.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, jade thermal fillers cannot form thermal conductivity paths inside the fibers, resulting in poor cooling effect.
By preparing iron tetraoxide and jade powder into high-thermal conduction particles, and setting a uniform magnetic field during the spinning process, the high-thermal conduction particles are arranged in an orientation within the fiber to form a thermal conduction path.
In the case of small amount of jade powder, the contact cooling effect of the fiber is significantly improved, and the moisture-absorbing and wicking performance of the fiber is improved while maintaining the strength of the fiber.
Smart Images

Figure CN119824571A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester fibers, and in particular to jade cooling fibers and a preparation method thereof. Background Art
[0002] Polyester fiber is widely used in the textile field due to its high strength and good shape retention. However, polyester fiber has poor moisture absorption and the fabric is hot and not breathable. Therefore, modifying it by physical or chemical means to improve the performance of polyester fiber is the future research and development direction. Jade is a symbol of Chinese civilization and has always been highly respected for its collection and health value. Jade is rich in trace elements and has the effect of releasing negative ions and far infrared. Long-term use can eliminate fatigue. In addition, compared with fiber materials, jade also has high thermal conductivity, so it is added to fibers by many textile practitioners to develop cool fibers.
[0003] Chinese patent CN202310436119.2 discloses a method for preparing a cool cross-shaped moisture-conducting quick-drying polyester fiber. The patent adds ice jade as a thermal conductive material to polyester fibers, and cooperates with a cross-shaped fiber cross-section to improve the fiber's moisture absorption, quick drying and contact coolness. Although ice jade itself has a high thermal conductivity and feels cool to the touch, the ice jade powder is distributed in a point-like manner inside the fiber and cannot form a heat conduction path. Therefore, after the fiber comes into contact with human skin, it cannot quickly extract the heat of the human body and dissipate it into the air, so the cool experience is not good. Chinese patent CN201110325475.4 discloses a method for preparing a cross-shaped normal pressure cationic dyeable cool polyester fiber. The patent blends mica masterbatch with cationic dyeable polyester to prepare a cross-shaped cross-section cool polyester fiber. However, the patent also has the problem that the mica thermal conductive powder cannot form a heat conduction path inside the fiber, and the cool effect of the fiber produced is not satisfactory.
[0004] The method of increasing the amount of jade added to improve the cooling effect of fibers will significantly reduce the fiber strength. Therefore, there is an urgent need in this field to develop a high thermal conductivity jade cooling fiber that can significantly improve the cooling effect and moisture absorption and perspiration performance of polyester fibers while reducing the amount of jade powder used. Summary of the invention
[0005] The purpose of the present invention is to solve the problem in the prior art that the jade thermal conductive filler cannot form a thermal conductive path inside the fiber, resulting in a poor cooling effect.
[0006] To achieve the above objectives, this application is implemented through the following technical solutions: The present application provides a jade cooling fiber, which is a polyester fiber prepared by melt spinning with hydrophilic polyester as the main raw material, and the fiber includes high thermal conductivity particles, which are oriented and arranged inside the fiber to form a thermal conductive path. In terms of mass percentage, the high thermal conductivity particles include 65% to 85% jade and 15% to 35% ferrosoferric oxide. Preferably, in terms of mass percentage, the fiber contains 0.3% to 1.4% of high thermal conductivity particles. Further, the fiber contains 0.18% to 1.2% jade and 0.04% to 0.5% ferrosoferric oxide.
[0007] As a further improvement of the present application, the jade is selected from one or more of nephrite, Taishan jade, rhodonite, and chlorite.
[0008] As a further improvement of the present application, the cross-sectional shape of the jade cooling fiber is a cross.
[0009] To achieve the above object, the present application also provides a method for preparing jade cooling fiber, comprising the following steps: S1. Preparation of high thermal conductive particles: jade powder, a first dispersant, and deionized water are mixed in a first preset ratio, stirred evenly to obtain a suspension, a first inorganic salt containing iron ions and a second inorganic salt containing ferrous ions are added to the suspension, and stirred evenly to obtain a mixed solution, the pH of the mixed solution is adjusted to 10 to 11.5, the mixed solution is placed at 40° C. for full reaction, filtered, washed, and dried to obtain high thermal conductive particles; S2, preparation of cooling masterbatch: after uniformly mixing the high thermal conductive particles, the first hydrophilic polyester chips, the second dispersant, and the coupling agent according to a second preset ratio, melt-extrude, and pelletize to obtain cooling masterbatch; S3, preparation of jade cool fiber: after the second hydrophilic polyester slice and the cool masterbatch are evenly mixed according to the third preset ratio, the jade cool fiber is obtained after spinning, cooling, drawing, oiling, cutting and drying processes in sequence, wherein, during the spinning process, a uniform magnetic field is set directly below the spinneret to orient the high thermal conductivity particles inside the fiber. Wherein: the first hydrophilic polyester slice in step S2 and the second hydrophilic polyester slice in step S3 are hydrophilic polyester slices of the same material. Preferably, during the spinning process, a uniform magnetic field perpendicular to the direction of the melt jet is set directly below the spinneret of the spinning assembly. Furthermore, the intensity of the magnetic field is 1T to 2T.
[0010] As a further improvement of the present application, in step S1, 10% to 20% of jade powder, 0.02% to 0.2% of the first dispersant, and 79.8% to 89.98% of deionized water are mixed in percentage by mass.
[0011] As a further improvement of the present application, in step S1, the jade powder is selected from one or more of nephrite, Taishan jade, rhodonite, and chlorite. Preferably, the average particle size of the jade powder is D90≤1 μm.
[0012] As a further improvement of the present application, in step S1, the molar ratio of the first inorganic salt to the second inorganic salt is 1 to 2.2.
[0013] As a further improvement of the present application, the first dispersant is sodium hexametaphosphate or sodium tripolyphosphate, the first inorganic salt is ferric chloride or ferric sulfate, and the second inorganic salt is ferrous chloride or ferrous sulfate.
[0014] As a further improvement of the present application, in step S1, the pH value of the mixed solution is adjusted using ammonia water or sodium hydroxide solution, and the dripping speed of the ammonia water or the sodium hydroxide solution is 0.5 drops / s.
[0015] As a further improvement of the present application, in step S1, the obtained high thermal conductive particles are ground and sieved to obtain high thermal conductive particles with an average particle size D90≤1.2 μm.
[0016] As a further improvement of the present application, in step S2, 10% to 20% of high thermal conductive particles, 74% to 88% of the first hydrophilic polyester chips, 1% to 4% of the second dispersant, and 1% to 2% of the coupling agent are mixed evenly in terms of mass percentage.
[0017] As a further improvement of the present application, in step S2, the second dispersant is selected from one or more of stearic acid, sodium hexametaphosphate or sodium dodecyl sulfate, and the coupling agent is selected from phosphate ester or titanate ester.
[0018] As a further improvement of the present application, in step S2, the temperature of the extrusion equipment for melt extrusion is 160°C to 260°C, and the screw speed of the extrusion equipment is 80r / min to 100r / min.
[0019] As a further improvement of the present application, in step S3, 93% to 97% of the second hydrophilic polyester chips and 3% to 7% of the cooling masterbatch are mixed uniformly in terms of mass percentage.
[0020] As a further improvement of the present application, in step S3, the spinning temperature is 270°C to 290°C, and the cooling temperature is 16°C to 20°C.
[0021] As a further improvement of the present application, in step S3, the cross-sectional shape of the jade cooling fiber is a cross.
[0022] The beneficial effects of this application are: 1) In the present application, ferroferric oxide and jade powder are prepared into high thermal conductivity particles, and the particles are added into the fiber spinning components. A uniform magnetic field perpendicular to the melt jet direction is set at the melt jet outlet of the spinning assembly, so that the high thermal conductivity particles are oriented and arranged inside the fiber to form a heat conduction path, thereby achieving a significant cool feeling on the fiber when a small amount of jade powder is used.
[0023] 2) The jade cooling fiber prepared by the present application has magnetic therapy and health care effects because it contains the magnetic substance ferroferric oxide inside, and jade is rich in trace elements. Long-term use of the jade cooling fiber prepared by the present invention is beneficial to health.
[0024] 3) The jade cooling fiber prepared in the present application has good spinnability during the spinning process due to the lower amount of jade powder used, and the spinneret holes will not be blocked during long-term production, and the fiber strength does not decrease significantly.
[0025] 4) The jade cool fiber prepared in the present application is made of hydrophilic polyester slices, and has a moisture regain of up to 1.2%, which overcomes the shortcomings of ordinary polyester with low moisture regain and dampness and airtightness, and improves its comfort in use. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram of the uniform magnetic field structure for the spinning process of this application; Figure 2 This is a schematic cross-sectional view of the oriented arrangement of thermally conductive particles within the jade cooling fiber prepared in the present application. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solution of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0028] In order to make the above-mentioned objects, features and advantages of the present application more obvious and easy to understand, the present application is further described in detail below in conjunction with specific implementation methods.
[0029] Example 1 This embodiment provides a jade cooling fiber, and the preparation method thereof is as follows: S1. Preparation of high thermal conductive particles: 15% jade powder, 0.1% first dispersant, and 84.9% deionized water are mixed by mass percentage and stirred evenly to form a stable suspension. A first inorganic salt containing iron ions and a second inorganic salt containing ferrous ions are added to the suspension and stirred evenly to obtain a mixed solution. Sodium hydroxide solution is added to the mixed solution while stirring until the pH of the mixed system is 11. After the mixed solution is reacted at a constant temperature of 40°C for 2 hours, the reaction product is filtered out and washed with deionized water to neutrality. Finally, the filtrate washed to neutrality is dried at 110°C to obtain jade powder loaded with ferroferric oxide, that is, high thermal conductive particles, and then the high thermal conductive particles are ground and sieved to a particle size of D90≤1.2μm. Among them, the jade powder comes from Taishan jade, and the particle size of the jade powder is D90≤1μm; the first dispersant is sodium hexametaphosphate; the first inorganic salt is ferric chloride, the second inorganic salt is ferrous chloride, the amount ratio of ferric chloride to ferrous chloride is 1.5:1, and the dripping speed of the sodium hydroxide solution is 0.5 drops / s; in the obtained high thermal conductive particles, the mass percentage of jade powder is 75%, and the remainder is ferrosoferric oxide.
[0030] S2. Preparation of cooling masterbatch: 15% high thermal conductive particles, 80% first hydrophilic polyester chips, 3% second dispersant, and 2% coupling agent are mixed evenly by mass percentage, and then melt-extruded and pelletized by a twin-screw extruder to obtain cooling masterbatch. Among them, the second dispersant is sodium hexametaphosphate and the coupling agent is phosphate ester. The twin-screw extruder is divided into 1-6 zones, and the temperatures from 1 to 6 zones are 160°C, 180°C, 200°C, 220°C, 240°C, and 260°C, respectively, and the screw speed is 100 rpm.
[0031] S3. Preparation of jade cool fiber: 95% of the second hydrophilic polyester chips and 5% of the cool masterbatch were mixed evenly by mass percentage, and then spun through a cross-shaped special-shaped hole spinneret, cooled, and then subjected to drawing, oiling, cutting, drying and other processes to obtain jade cool fiber. The spinning temperature was 280°C and the annular air temperature was 18°C. A uniform magnetic field was set directly below the spinneret, the direction of the magnetic field was perpendicular to the direction of the melt jet, and the magnetic field strength was 2T.
[0032] The first hydrophilic polyester slice in step S2 and the second hydrophilic polyester slice in step S3 are hydrophilic polyester slices made of the same material.
[0033] Example 2 This embodiment provides a jade cooling fiber, and the preparation method thereof is as follows: S1. Preparation of high thermal conductive particles: 10% jade powder, 0.02% first dispersant, and 89.98% deionized water are mixed by mass percentage, and stirred evenly to form a stable suspension. A first inorganic salt containing iron ions and a second inorganic salt containing ferrous ions are added to the suspension, and stirred evenly to obtain a mixed solution. Sodium hydroxide solution is added to the mixed solution, stirring while adding until the pH of the mixed system is 11.5. After the mixed solution is reacted at a constant temperature of 40°C for 2 hours, the reaction product is filtered out and washed with deionized water to neutrality. Finally, the filtrate washed to neutrality is dried at 110°C to obtain jade powder loaded with ferroferric oxide, that is, high thermal conductive particles, and then the high thermal conductive particles are ground and sieved to a particle size of D90≤1.2μm. Among them, the jade powder comes from Taishan jade, and the particle size of the jade powder is D90≤1μm; the first dispersant is sodium hexametaphosphate; the first inorganic salt is ferric chloride, the second inorganic salt is ferrous chloride, the amount ratio of ferric chloride to ferrous chloride is 2.2:1, and the dripping speed of the sodium hydroxide solution is 0.5 drops / s; in the obtained high thermal conductive particles, the mass percentage of jade powder is 85%, and the remainder is ferrosoferric oxide.
[0034] S2. Preparation of cooling masterbatch: 10% high thermal conductive particles, 74% first hydrophilic polyester chips, 4% second dispersant, and 2% coupling agent are mixed evenly by mass percentage, and then melt-extruded and pelletized by a twin-screw extruder to obtain cooling masterbatch. Among them, the second dispersant is stearic acid and the coupling agent is phosphate. The twin-screw extruder is divided into 1-6 zones, and the temperatures from the 1st to the 6th zone are 160°C, 180°C, 200°C, 220°C, 240°C, and 260°C, respectively, and the screw speed is 90 rpm.
[0035] S3. Preparation of jade cool fiber: 97% of the second hydrophilic polyester chips and 3% of the cool masterbatch were mixed evenly by mass percentage, and then spun through a cross-shaped special-shaped hole spinneret, cooled, and then subjected to drawing, oiling, cutting, drying and other processes to obtain jade cool fiber. The spinning temperature was 280°C and the annular air temperature was 18°C. A uniform magnetic field was set directly below the spinneret, the direction of the magnetic field was perpendicular to the direction of the melt jet, and the magnetic field strength was 1.5T.
[0036] Wherein: the first hydrophilic polyester slice in step S2 and the second hydrophilic polyester slice in step S3 are hydrophilic polyester slices made of the same material.
[0037] Example 3 A method for preparing jade cooling fiber is as follows: S1. Preparation of high thermal conductive particles: In terms of mass percentage, 20% jade powder, 0.2% first dispersant, and 79.8% deionized water are mixed and stirred evenly to form a stable suspension. A first inorganic salt containing iron ions and a second inorganic salt containing ferrous ions are added to the suspension and stirred evenly to obtain a mixed solution. Ammonia water is added to the mixed solution while stirring until the pH of the mixed system is 10. After the mixed solution is placed at 40°C for constant temperature reaction for 2 hours, the reaction product is filtered out and washed with deionized water until neutral. Finally, the filtrate washed to neutral is dried at 110°C to obtain jade powder loaded with ferroferric oxide, that is, high thermal conductive particles. The high thermal conductive particles are further ground and sieved to an average particle size D90≤1.2μm. Among them: the jade powder comes from Taishan jade, and the particle size of the jade powder is D90≤1μm; the first dispersant is sodium tripolyphosphate; the first inorganic salt is ferric sulfate, the second inorganic salt is ferrous sulfate, the molar ratio of ferric sulfate to ferrous sulfate is 1:1, and the dripping speed of the ammonia water is 0.5 drops / s; in the obtained high thermal conductive particles, the mass percentage of jade powder is 66%, and the remainder is ferrosoferric oxide.
[0038] S2. Preparation of cool masterbatch: 20% high thermal conductive particles, 88% first hydrophilic polyester chips, 1% second dispersant, and 1% coupling agent were mixed evenly by mass percentage, and then melt-extruded and pelletized by a twin-screw extruder to obtain a cool masterbatch. Among them, the second dispersant is sodium dodecyl sulfate and the coupling agent is titanate. The twin-screw extruder is divided into 1-6 zones, and the temperatures from 1 to 6 zones are 160°C, 180°C, 200°C, 220°C, 240°C, and 260°C, respectively, and the screw speed is 80r / min.
[0039] S3. Preparation of jade cool fiber: 93% of the second hydrophilic polyester chips and 7% of the cool masterbatch were mixed evenly by mass percentage, and then spun through a cross-shaped special-shaped hole spinneret, cooled, and then subjected to drawing, oiling, cutting, drying and other processes to obtain jade cool fiber. The spinning temperature was 270°C, the annular air temperature was 16°C, and a uniform magnetic field was set directly below the spinneret, the direction of the magnetic field was perpendicular to the direction of the melt jet, and the magnetic field strength was 1T.
[0040] Wherein: the first hydrophilic polyester slice in step S2 and the second hydrophilic polyester slice in step S3 are hydrophilic polyester slices made of the same material.
[0041] Example 4 The difference between this embodiment and embodiment 1 is that in step S1, the jade used is nephrite.
[0042] Example 5 The difference between this embodiment and embodiment 1 is that in step S1, the jade used is rhodonite.
[0043] Example 6 The difference between this embodiment and embodiment 1 is that in step S1, the jade used is chlorite.
[0044] Comparative Example 1 The difference between this comparative example and Example 1 is that in step S1, the jade used is muscovite.
[0045] Comparative Example 2 The difference between this comparative example and Example 1 is that step S1 is not performed, and Taishan jade powder with a particle size D90≤1.2 μm is directly used as high thermal conductive particles for granulation in step S2, and then step S3 is performed for spinning.
[0046] Comparative Example 3 The difference between this comparative example and Example 1 is that in step S3, no magnetic field is set during the spinning process.
[0047] Comparative Example 4 The difference between this comparative example and Example 1 is that: step S1 is not performed, and muscovite powder with a particle size D90≤1.2 μm is directly used as high thermal conductive particles for granulation in step S2. In step S3, no magnetic field is set during the spinning process.
[0048] Comparative Example 5 The difference between this comparative example and Example 1 is that conventional polyester chips are used in place of hydrophilic polyester chips in step S2 and in the middle of step S3.
[0049] Comparative Example 6 The difference between this comparative example and Example 1 is that conventional circular spinnerets are used in step S3 to prepare circular cross-section polyester fibers.
[0050] Comparative Example 7 The difference between this comparative example and Example 1 is that steps S1 and S2 are not performed, and hydrophilic polyester chips are directly used for spinning in step S3.
[0051] The fibers obtained in the above embodiments and comparative examples were subjected to strength tests according to GB / T 14337-2022 Test method for tensile properties of chemical staple fibers. The fabrics made of the fibers obtained in the above embodiments and comparative examples were subjected to contact coolness performance tests according to GB / T 35263-2017 Testing and evaluation of instantaneous coolness of textiles. The fibers obtained in the above embodiments and comparative examples and lyocell blended fabrics were subjected to continuous coolness performance tests according to T / CNGA 23-2021 Testing and evaluation of continuous coolness of clothing, wherein the jade coolness fiber accounts for 30% and the lyocell fiber accounts for 70% in the blended fabrics. The test results are shown in Table 1 below.
[0052] Table 1 Test results of breaking strength, instantaneous cool feeling on contact and continuous cool feeling on contact.
[0053]
[0054] It can be seen from each embodiment in Table 1 that the jade cool fiber prepared by the present invention has excellent tensile fracture strength, and the fabric prepared by the jade cool fiber has excellent contact instant coolness and contact continuous coolness. It can be seen from Examples 1-3 that the higher the amount of jade thermal conductive particles added to the load ferroferric oxide magnetic material, the greater the contact instant coolness of the jade fiber. This is because under the action of the magnetic field, the higher the content of thermal conductive particles, the more thermal conductive paths formed inside the fiber, which is conducive to heat extraction and dissipation. On the other hand, the amount of thermal conductive particles added increases, and the fiber strength has a downward trend, because inorganic thermal conductive particles may form stress defects and stress concentration inside the fiber, deteriorating the fiber strength. Nevertheless, the present invention, by reasonably controlling the amount of thermal conductive particles added, while ensuring the cool effect, makes the fracture strength of the jade cool fiber prepared above the first-class product index specified in "GB / T14464-2017 Polyester Staple Fiber".
[0055] By comparing Example 1, Example 4-6 with Comparative Example 1, it can be seen that after the preferred jade raw material is replaced with muscovite, under the same amount of heat-conducting particles added, the cool feeling of the jade cool fiber made by the comparative example decreases at the moment of contact. This is because the preferred jade raw material in the embodiment contains a large amount of iron elements, which have a synergistic effect with the magnetic ferroferric oxide loaded on the surface of the jade powder, and have a stronger response to the external magnetic field, which is conducive to the orientation of the heat-conducting particles to form a heat-conducting path. However, muscovite does not contain iron elements. Under the action of the magnetic field, the heat-conducting particles are driven by the magnetic ferroferric oxide loaded on the surface to produce an orientation arrangement.
[0056] By comparing Example 1, Examples 4-6 with Comparative Example 2, it can be seen that the instantaneous cool feeling of the comparative example fiber is significantly reduced. This is because, although the preferred jade powder contains a large amount of iron, when the surface is not loaded with magnetic ferroferric oxide, the thermal conductive particles are not sufficiently responsive to the magnetic field, and the number of thermal conductive paths formed in the fiber is reduced.
[0057] By comparing Example 1, Examples 4-6 with Comparative Example 3, it can be seen that in the absence of an external magnetic field, the instantaneous coolness of the comparative fiber is greatly reduced. This is because the external magnetic field is the driving factor for the orientation of the thermal conductive particles. If there is no magnetic field, the thermal conductive particles are randomly arranged inside the fiber and cannot be oriented to form a heat conduction path. The thermal conductive particles basically cannot enhance the cooling effect.
[0058] By comparing Example 1, Examples 4-6 with Comparative Example 4, it can be seen that according to the scheme of the prior art, the mica masterbatch is introduced into the melt spinning process, and the cooling effect of the comparative fiber produced is far lower than the cooling effect of the example fiber in the present technical scheme. This is because the present application uses jade containing a large amount of iron elements, which can form a heat conduction path inside the fiber under the action of the external magnetic field with ferroferric oxide, thereby enhancing the instantaneous coolness of the fiber when it is touched.
[0059] By comparing Example 1, Example 4-6 with Comparative Example 5, it can be seen that after the hydrophilic polyester slices are replaced with conventional polyester slices, the instantaneous cool feeling of the contact of the jade cool fiber produced is slightly reduced, and it also cannot meet the standard of continuous cool feeling on contact. This is because the moisture regain of the fiber made of hydrophilic polyester is higher, which can make the fiber contain more water, and the thermal conductivity of water is much higher than that of polyester material, which has the effect of improving the thermal conductivity of the fiber and thus improving the instantaneous cool feeling on contact to a certain extent. At the same time, the continuous cool feeling on contact does not meet the standard because the conventional polyester material has poor hydrophilicity, resulting in excessive evaporation of water during the continuous cool feeling on contact test process, and the water has completely evaporated before the test process is completed. The ability to maintain continuous cool feeling on contact by absorbing heat through water evaporation is lost in the later stage of the test process. On the other hand, conventional polyester materials hardly absorb water, and the water added during the test process will form a larger wetting area on the fabric, reducing the water content per unit area of the fabric test area. Therefore, when the test site contacts the temperature probe, the water will evaporate faster, which is not conducive to maintaining continuous cool feeling on contact.
[0060] By comparing Example 1, Examples 4-6 with Comparative Example 6, it can be seen that, under the condition that other conditions remain unchanged, the change in the cross-sectional shape of the fiber has little effect on the instantaneous cool feeling of contact, but significantly reduces the continuous cool feeling of the fiber on contact. This is because the cross-sectional hydrophilic polyester has a certain hydrophilicity, and can be combined with lyocell fiber in the blended fabric to adsorb the liquid water dripped during the test around the temperature probe, and the capillary effect of the cross-sectional fiber continuously evaporates water and absorbs heat to maintain the low temperature state of the fabric around the probe, that is, it has a continuous cool effect.
[0061] By comparing Example 1, Examples 4-6 with Comparative Example 7, it can be seen that the continuous cool feeling of the fiber of Comparative Example 7 can reach the secondary standard, but its instantaneous cool feeling effect is significantly reduced. That is, by preferably selecting jade with high iron content, the load of magnetic material ferroferric oxide and the drive of the external magnetic field, a large number of heat conduction paths are formed inside the fiber, which is a very important factor affecting the instantaneous cool feeling effect of the fiber. The continuous cool feeling of contact is achieved by hydrophilic polyester fiber and controlling the cross-sectional shape of the fiber.
[0062] Although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0063] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present application. They are not intended to limit the scope of protection of the present application. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present application should be included in the scope of protection of the present application.
Claims
1. A jade cooling fiber, characterized in that: The fiber is a polyester fiber prepared by melt spinning with hydrophilic polyester as the main raw material. The fiber includes high thermal conductivity particles. The high thermal conductivity particles are oriented and arranged inside the fiber to form a thermal conduction path. Calculated by mass percentage, the high thermal conductivity particles include 65% to 85% jade and 15% to 35% ferrosoferric oxide.
2. The method for preparing the jade cool fiber according to claim 1, characterized in that: The steps include: S1. Preparation of high thermal conductive particles: jade powder, a first dispersant, and deionized water are mixed in a first preset ratio, stirred evenly to obtain a suspension, a first inorganic salt containing iron ions and a second inorganic salt containing ferrous ions are added to the suspension, and stirred evenly to obtain a mixed solution, the pH of the mixed solution is adjusted to 10 to 11.5, the mixed solution is placed at 40° C. for full reaction, filtered, washed, and dried to obtain high thermal conductive particles; S2, preparation of cooling masterbatch: mixing the high thermal conductive particles, the first hydrophilic polyester chips, the second dispersant, and the coupling agent in a second preset ratio, melt-extruding, and pelletizing to obtain cooling masterbatch; S3. Preparation of jade cooling fiber: after the second hydrophilic polyester chips and the cooling masterbatch are uniformly mixed according to the third preset ratio, the fibers are successively subjected to spinning, cooling, drawing, oiling, cutting and drying steps to obtain jade cooling fibers. During the spinning process, a uniform magnetic field is set just below the spinneret so that the high thermal conductive particles are oriented inside the fiber.
3. The method for preparing the jade cool fiber according to claim 2, characterized in that, In step S1, the jade powder is selected from one or more of nephrite, Taishan jade, rhodonite, and chlorite.
4. The method for preparing the jade cool fiber according to claim 2, characterized in that, In step S1, the molar ratio of the first inorganic salt to the second inorganic salt is 1 to 2.
2.
5. The method for preparing the jade cool fiber according to claim 4, characterized in that: In step S1, the first dispersant is sodium hexametaphosphate or sodium tripolyphosphate, the first inorganic salt is ferric chloride or ferric sulfate, and the second inorganic salt is ferrous chloride or ferrous sulfate.
6. The method for preparing the jade cool fiber according to claim 2, characterized in that: In step S1, the pH value of the mixed solution is adjusted by using ammonia water or sodium hydroxide solution, and the dropping speed of the ammonia water or the sodium hydroxide solution is 0.5 drops / s.
7. The method for preparing the jade cool fiber according to claim 2, characterized in that: In step S2, the second dispersant is selected from one or more of stearic acid, sodium hexametaphosphate or sodium dodecyl sulfate, and the coupling agent is selected from phosphate ester or titanate ester.
8. The method for preparing the jade cool fiber according to claim 2, characterized in that: In step S2, the temperature of the extrusion equipment for melt extrusion is 160°C to 260°C, and the screw speed of the extrusion equipment is 80r / min to 100r / min.
9. The method for preparing the jade cool fiber according to claim 2, characterized in that: In step S3, the spinning temperature is 270°C to 290°C, and the cooling temperature is 16°C to 20°C.
10. The method for preparing the jade cooling fiber according to claim 2, characterized in that: In step S3, the cross-sectional shape of the jade cooling fiber is a cross.
Citation Information
Patent Citations
Cross cool easy cation-dyeable polyester (ECDP) fiber and production method thereof
CN102409430B
Cool-feeling cross-section moisture-conducting quick-drying polyester fiber as well as preparation method and application thereof
CN116288793A
Jade cool regenerated cellulose fiber and preparing method thereof
CN106222776A
Cool quick-drying hydrophilic polyester fiber and preparation method thereof
CN107012531A
Heat-conducting wave-absorbing silica gel composite material and preparation method thereof
CN112194903A
Cited By
A nylon material and a method for producing the same
CN122832492A